Organizing Micro Economic Scale through Women Empowerment Group (Descriptive Study in Pesanggrahan Village) - Jannah, Andita Uzlifatil; Mulyono, Joko (Jurnal ENTITAS SOSIOLOGI, 2018)
The unemployment problem is triggered by the imbalance of job opportunities and the number of job seekers, especially in rural areas. Besides, restrictions on working women based on customs and norms in the village make it difficult for women to find work. The view that women should focus on domestic and family matters. It limits women to work to help improve the family economy. Thus, empowerment for women through community empowerment group is needed to be able to carry out economic activities without having to leave their duties as a housewife. The theoretical framework of this study is the theory of liberal feminism gender based on women's freedom and equality. This study uses a qualitative method and purposive sampling. Data collected through observation, interviews, and documentation. The results of this study are that empowering women can do business on a micro-scale to help increase family income; Also, this research explains about equality between women and men, and forms of women's participation, democracy, transparency, and accountability in women's empowerment programs. Keywords: Self-help groups, Gender equality, government programs Referensi: Idrus, Muhammad. 2009. Metode Penelitian Ilmu Sosial. Cetakan Kedua. Jakarta: Erlangga Irwan, P. 2006. Penelitian Kualitatif dan kuantitatif untuk ilmu-ilmu sosial. Depok: FISIP UI PRES Jamaluddin, Dr. Adon Nasrullah. 2015. Sosiologi Perkotaan. Surakarta : Pustaka Setia Materi Pelatihan Tim Vrifikasi PNPM-MP Keamatan Jangkar Tahun 2010 Moleong, Lexy. 2008. Metode penelitian kualitatif. Bandung: Remaja Rosdakarya Nazir. 1988. Metode Penelitian. Jakarta: Galia Indonesia Profil Desa Pesanggrahan Tahun 2018 Satori Djam’an, Komariah Aan. 2012. Metodologi Penelitian Kualitatif. Bandung :Alfabeta Sugihastuti, Saptiawan Itsna Hadi. 2007. Gender & Inferioritas Perempuan. Yogyakarta: Pustaka Pelajar Sugiyono. 2005. Metode Penelitian Kualitatif. Bandung : Alfabeta